Renal angiomyolipoma during pregnancy: Case report and literature review - Çetin, Cihan (Turk J Obstet Gynecol, 2015)
Renal angiomyolipoma is a rare tumor that can be either sporadic or found together with tuberous sclerosis or pulmonary lymphangioleiomyomatosis. These tumors are hormone sensitive and therefore tend to grow during pregnancy and their main complication is the risk of rupture. Optimal management is still controversial because there are very few cases reported in the literature. We expect that the case of our patient, who delivered her baby vaginally at 36 weeks of gestation and underwent definitive treatment (nephrectomy) thereafter, to further enhance the knowledge about the management of these rare tumors during pregnancy.